The Fuente de la Sábana and the baroque stage of the suburban villa El Bosque de Béjar - José Muñoz Domínguez (VLC Arquitectura, 2018)
Most of the studies published on the suburban village El Bosque de Béjar (Salamanca) focus on its Renaissance period, when it was created by Duke Francisco de Zúñiga y Sotomayor, leaving in the background the contributions of other later dukes. The article documents the Baroque reforms of French inspiration projected in the period 1705-1727 by Juan Manuel Diego Lopez de Zúñiga y Castro, XI attenuated, who began with the construction of the so-called Fuente de la Sábana (ca. 1705) and included a walk with “gazon” bands, a “potager”, large pots with orange trees, a park and a “fondería” (distillery) attended by botanist masters. The projects, probably inspired by the Abbe Emmanuel Jouin, were partly executed and are among the earlier ones of the first Bourbon period within the environment of the nobility.